2006
DOI: 10.1002/pmic.200401351
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analyses ofOryza sativa mature pollen reveal novel proteins associated with pollen germination and tube growth

Abstract: As a highly reduced organism, pollen performs specialized functions to generate and carry sperm into the ovule by its polarily growing pollen tube. Yet the molecular genetic basis of these functions is poorly understood. Here, we identified 322 unique proteins, most of which were not reported previously to be in pollen, from mature pollen of Oryza sativa L. ssp japonica using a proteomic approach, 23% of them having more than one isoform. Functional classification reveals that an overrepresentation of the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
254
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(268 citation statements)
references
References 66 publications
10
254
2
Order By: Relevance
“…2). ␤-1,4-Xylanase, a main pollen coat protein of maize (20) and rice (14), which is deposited into the pollen coat from tapetal cells of anthers (20) and whose transcripts are absent in MPGs and GPGs (Fig. 3), was present at a high level in MPGs but barely detectable in GPGs (Fig.…”
Section: And E)mentioning
confidence: 99%
See 2 more Smart Citations
“…2). ␤-1,4-Xylanase, a main pollen coat protein of maize (20) and rice (14), which is deposited into the pollen coat from tapetal cells of anthers (20) and whose transcripts are absent in MPGs and GPGs (Fig. 3), was present at a high level in MPGs but barely detectable in GPGs (Fig.…”
Section: And E)mentioning
confidence: 99%
“…But numerous studies have revealed that some or all proteins in the pollen coat, a specialized layer outside the wall, and several pollen wall-associated species, either from pollen itself or from sporophytic tissues of anthers, are releasable during pollen germination (14,20); and after pollination and germination on the stigma, the germinating pollen will release some interior proteins for interaction with the stigma to facilitate tube growth in pistils. Thus, the RVreduced proteins or those that have disappeared in the germinated pollen may result from real down-regulated expression and/or release of coat/wall-associated and pollen-interior proteins into the germination medium.…”
Section: And E)mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies including proteomic studies focused on differences between the expression levels of pollen and sporophytic tissue or of different states in pollen development (Becker et al, 2003;Honys and Twell, 2003;Pina et al, 2005;Bock et al, 2006). Only few studies focused on pollen tube growth (Dai et al, 2006;Wang et al, 2008;Grobei et al, 2009;Qin et al, 2009). Although metabolic pathway networks were reconstructed from these data (Boavida et al, 2005;Colaço et al, 2012) using the MAPMAN tool (Thimm et al, 2004), the correlation between the presence of mRNA, the amount of protein, and its specific activity remains uncertain (Gry et al, 2009;Taniguchi et al, 2010).…”
mentioning
confidence: 99%
“…Studies focusing solely on the proteome of the male gametophyte have been performed in Arabidopsis and Pinus strobus (Fernando, 2005;Holmes-Davis et al, 2005). Recent proteomic investigations of pollens from Arabidopsis, rice, and gymnosperms have provided opportunities to complement the information derived from transcriptomic analysis and offered new insights into the mechanisms underlying pollen functional specification (Noir et al, 2005;Dai et al, 2006Dai et al, , 2007Sheoran et al, 2006). However, pollen tube development in conifers (gymnosperm) differs in several ways from that in angiosperms, such as in the extended growth period, relatively slow growth rate, and extremely delayed gametogenesis, which represent a major evolutionary divergence in male gametophyte development in the flowering plants (Fernando, 2005Williams, 2008).…”
mentioning
confidence: 99%